Madelung Deformity - A Case Report with Literature Review. (Bangladesh Journal of Neuroscience, 2014)
Madelung deformity (MD) is a rare autosomaldominant disordercharacterized by epiphyseal growth plate disturbance in distal ulnar sidewhereina progressive ulnar and volar tilt of itsarticular surface occurs in associationwith a dorsal subluxation of the distalulna.Diagnosis of the diseaseis by correlation of clinical data with radiological findings and genetic transmission.In this study, radiographic findings ofa 16 years old female patient progressive bilateral wrist joint deformity and bowing of distal end of forearm without significant functional impairment and systemic complaints and diagnosed as Primary Madelung deformity, is reported. Bangladesh Journal of Neuroscience 2011; Vol. 27 (2) : 101-104 DOI: http://dx.doi.org/10.3329/bjn.v27i2.17577